2011
DOI: 10.5194/bg-8-1721-2011
|View full text |Cite
|
Sign up to set email alerts
|

Importance of crop varieties and management practices: evaluation of a process-based model for simulating CO<sub>2</sub> and H<sub>2</sub>O fluxes at five European maize (<i>Zea mays</i> L.) sites

Abstract: Abstract. This paper is a modelling study of crop management impacts on carbon and water fluxes at a range of European sites. The model is a crop growth model (STICS) coupled with a process-based land surface model (ORCHIDEE). The data are online eddy-covariance observations of CO 2 and H 2 O fluxes at five European maize cultivation sites. The results show that the ORCHIDEE-STICS model explains up to 75 % of the observed daily net CO 2 ecosystem exchange (NEE) variance, and up to 79 % of the latent heat flux … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…This suggests that modifying the model's root water uptake function and (or) incorporating hydraulic redistribution into the model does not impact the model's performance when soil moisture is readily available during the wet season. Most biases in the simulated NEE during the wet season at all three sites result from errors in the simulated ecosystem respiration by CABLE, as also found for other land surface models [Baker et al, 2008;Li et al, 2011]. During dry seasons, however, the performances of the default CABLE and the other two configurations with either modification of an alternative root water uptake function or a hydraulic redistribution function were much poorer than the simulations including both revised root functions (as in S4).…”
Section: Sensitivity Analysissupporting
confidence: 57%
“…This suggests that modifying the model's root water uptake function and (or) incorporating hydraulic redistribution into the model does not impact the model's performance when soil moisture is readily available during the wet season. Most biases in the simulated NEE during the wet season at all three sites result from errors in the simulated ecosystem respiration by CABLE, as also found for other land surface models [Baker et al, 2008;Li et al, 2011]. During dry seasons, however, the performances of the default CABLE and the other two configurations with either modification of an alternative root water uptake function or a hydraulic redistribution function were much poorer than the simulations including both revised root functions (as in S4).…”
Section: Sensitivity Analysissupporting
confidence: 57%
“…Therefore, we expect that the performance of CLM can be improved if it is coupled to a crop model which can treat specific plant traits and include management practices. Li et al (2011) found that crop variety and management factors like irrigation, fertilization and planting date have a significant impact on NEE (and evapotranspiration) for the coupled LSM-crop model ORCHIDEE-STICS. Wu et al (2016) showed that a crop model coupled to the LSM ORCHIDEE, combined with assimilation of many different data types, was able to reproduce many measurement data up to the measurement uncertainty, whereas other remaining errors could be related to management activities which were not correctly represented in the model.…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, we expect that the performance of CLM can be improved if it is coupled to a crop model which can treat specific plant traits and include management practices. Li et al (2011) found that crop variety and management factors like irrigation, fertilization and planting date have a significant impact on NEE (and evapotranspiration) for the coupled LSM-crop model ORCHIDEE-STICS. Wu et al (2016) showed that a crop model coupled to the LSM ORCHIDEE, combined with assimilation of many different data types, was able to reproduce many measurement data up to the measurement uncertainty, whereas other remaining errors could be related to management activities which were not correctly represented in the model.…”
Section: Discussionmentioning
confidence: 98%
“…restrial compartments at the regional level. Therefore, comprehensive input and evaluation data are available for the catchment, including information on land use (Lussem and Waldhoff, 2013), LAIs (Ali et al, 2015;Reichenau et al, 2016) and EC data (Schmidt et al, 2012;Graf et al, 2014;Kessomkiat et al, 2013;Post et al, 2015).…”
Section: The Rur Catchmentmentioning
confidence: 99%
See 1 more Smart Citation